Zasady ustalania wartości bankowo-hipotecznej nieruchomości - Półtorak, Bogusław (The Rules of Mortgage Lending Value Estimation in Poland, 2006)
Financing of real estate market is based mainly on mortgage credits. It is usually connected with Instituting of a mortgage. It is very important to evaluate properly the value of a real estate when a credit agreement lasts. But in terms of estimation of mortgage lending value there is no single law lie, In order to use valuation in the future, its realism and taking the diversification of real estate market into account are essential. It could be corrected through cadastral system with information on real estate and evaluation of their values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 486-493